A photoswitchable rotaxane operating in monolayers on solid support. Issue 100 (30th November 2016) - Schwarz, Felix B.; Heinrich, Thomas; Lippitz, Andreas; Unger, Wolfgang E. S.; Schalley, Christoph A.
Abstract : A novel photoswitchable rotaxane was synthesised and its switching behaviour in solution and on solid support was studied. Abstract : A novel photoswitchable rotaxane was synthesised and its switching behaviour in solution was analysed with NMR and UV-Vis. A monolayer of rotaxanes was deposited on glass surfaces and the on-surface photoswitching was investigated. Angle-resolved NEXAFS spectra revealed a preferential orientation that reversibly changes upon switching.